Flexible exchange rates and international business - Blin, John M.; Greenbaum, Stuart I.; Jacobs, Donald P.; J.L. Kellogg Graduate School of Management; British-North American Committee ([London] : British-North American Committee, 1981)
The book is an assessment of experience and behavior among some important firms and institutions in the United States, United Kingdom and Canada. It examines how the firms involve in international operations, perceive, measure, monitor, and control their foreign exchange risks These firms range from those engaged in extractive, processing and manufacturing activities to those providing various financial services.
"This report was produced in collaboration with the J.L. Kellogg Graduate School of Management, Northwestern University."
Includes bibliographical references.
usc 19/04/18
Loans
Keywords: Foreign exchange rates; Commerce